(untitled) (Global Journal of Human-Social Science, 2012)
Despite the legislative frameworks put in place to enable the preservation of natural resources it is discovered that conflicts undermine the sustainable conservation ofnatural resources The paper examines the nature and intensity of conflicts within the Park while highlighting the critical causes for conflicts within the area A total of three hundred and ninetyfive questionnaires were distributed to eight study communities and the National Park management to elicit information on the factors that account for conflicts in the park Findings show that conflicts exist in the park owing to a number of factors which include park location and objection of the communities to the restrictions imposed on access to natural resources These collectively manifest as threats to the communities and the park objectives The factors accounting for this are identified to include lack of adequate employment of community members by Park management lack of compensation by the park management to community unemployment closeness of park boundary to communities and the restrictions of livelihood sources of the communities The study advocates for community enlightenment and the adoption of participatory approaches in creating and managing the National Park